Language Rights as Human Rights: Drawing upon Three Opposed Perspectives. Do Migrants Have Language Rights? - Klinytskyi, Illia; Coady, Maria (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
This article was created as part of research "The language rights protection standard for beneficiaries of international protection in Europe: A new legal approach to harmonize integration" financed by the NCN (reg. no 2022/45/N/HS5/00961). This article describes the multifaceted concept of language rights (LRs), exploring its real limits through three theoretical lenses: linguistic, geo-based, and as the rights of migrants. The linguistic perspective questions how a precise definition of language can be established, emphasizing the intrinsic value of all languages in communication, cultural preservation, diversity, and personal development. The geo-based approach posits LRs as collective rights developed by the state, essential for ethnic communities localized in specific geographical areas, their cultural identity, and self-determination. Examining LRs as migrant rights, the article stresses the individual and collective aspects, asserting their crucial role in ensuring inclusion, integration, and fair treatment. The study also scrutinizes language rights in compulsory education, comparing the implementations in the USA and Poland, shedding light on practical legal challenges. This comprehensive analysis aims to enrich the discourse on language rights, recognizing their pivotal role in fostering cultural diversity, social cohesion, and equitable integration, especially for minoritised groups like migrants.